Pola Evaluasi Pembelajaran PKn pada Program Moving Class di SMA Negeri 4 Banjarmasin - Fadillah, Rezky (Lambung Mangkurat University Indonesia, 2015)
Civics lesson evaluation that should be an important part of the learning process. In the evaluation of learning for more convenience needed a pattern which is used to execute teachers. With proper evaluation it is expected that the objective of the learning process was also fulfilled. Related to the learning process moving class is one program that is expected as a solution easier than learning system implemented. Therefore, this study wanted to examine various patterns of evaluation carried out in the school SMAN 4 Banjarmasin, when the school used as a moving class learning system. The results of this study indicate that the pattern of evaluations carried out civics lesson is based on the first 3 stages is important that the evaluation plan consisting of: determining the timing of evaluations and deliver learning. Then determine the type of evaluation used, further evaluation is aligning with Competence Standard, Basic Competence, Indicators, and the last is to choose the evaluation instrument and grating Making Problem. The second stage is the implementation of learning evaluation consisting of: Observations, Data Collection and Reporting scoring. The third stage: Processing and Analysis about the evaluation results.Â Keywords: Evaluation Patterns, moving class.Â